2011
DOI: 10.1016/j.ajodo.2010.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapid maxillary expansion on the cranial and circummaxillary sutures

Abstract: Introduction The aim of this study was to determine whether the orthopedic forces of rapid maxillary expansion cause significant quantitative changes in the cranial and the circummaxillary sutures. Methods Twenty patients (mean age, 12.3 ± 1.9 years) who required rapid maxillary expansion as a part of their comprehensive orthodontic treatment had preexpansion and postexpansion computed tomography scans. Ten cranial and circummaxillary sutures were located and measured on one of the axial, coronal, or sagitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 30 publications
9
87
0
1
Order By: Relevance
“…The effect of RME is not limited to the maxillary alveolar process but is also seen on adjacent structures, including the cranial and circummaxillary sutures. 39 In the present study, RME had significant effects at the level of the zygomaticomaxillary suture and nasal bone, but not in the frontozygomatic and frontomaxillary sutures (triangular expansion pattern). Finite element analysis of the stress distribution with RME shows high tensile stress at the zygomaticomaxillary suture, except along its anteromedial surface.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The effect of RME is not limited to the maxillary alveolar process but is also seen on adjacent structures, including the cranial and circummaxillary sutures. 39 In the present study, RME had significant effects at the level of the zygomaticomaxillary suture and nasal bone, but not in the frontozygomatic and frontomaxillary sutures (triangular expansion pattern). Finite element analysis of the stress distribution with RME shows high tensile stress at the zygomaticomaxillary suture, except along its anteromedial surface.…”
Section: Discussionmentioning
confidence: 79%
“…These appliances are designed to provide more uniform expansion of the palate and to inhibit alveolar tipping. 5,44 Compared to the slight negative expansion (constriction) of the frontomaxillary suture, noted for all groups in the present study (Table 1), Ghoneima et al 39 reported a small but significant increase (0.1 mm) in the width at the frontomaxillary suture with a bonded RME in a group of children with mean age of 12 years (range 8-15 years). However, the magnitude of the difference between the studies is small (,1 mm), so it is relatively insignificant compared to the overall triangular pattern of expansion noted in both studies.…”
Section: Discussionmentioning
confidence: 89%
“…A meta-analysis was not performed for this reason. Twenty-one studies 3,4,6,8,9,15,[18][19][20][22][23][24][25][26][28][29][30][31][32][33][34] were retrospective, five studies 7,11,12,16,17 were prospective, and four studies 5,10,21,27 were prospective and randomized. Six studies 10,18,[22][23][24]33 compared the results with a control group of the same age, and eight studies 4,6,10,12,22,[32][33][34] analyzed the long-term effects of RME.…”
Section: Resultsmentioning
confidence: 99%
“…Application of the inclusion and exclusion criteria and follow-up on the referred studies identified 30 relevant publications (Figure 1). [3][4][5][6][7][8][9][10][11][12][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Heterogeneity of the results of the investigations with similar technique of maxillary expansion was high (.85%). A meta-analysis was not performed for this reason.…”
Section: Resultsmentioning
confidence: 99%
“…Expansion occurs when the force applied to the teeth and maxilla exceeds the limits needed for tooth movement. 1 The applied force causes widening and gradual opening of the midpalatal suture, bending of the alveolar processes, and dental tipping.…”
Section: Introductionmentioning
confidence: 99%